2007
DOI: 10.1121/1.2723655
|View full text |Cite
|
Sign up to set email alerts
|

Quieting Weinberg 5C: A case study in hospital noise control

Abstract: Weinberg 5C of Johns Hopkins Hospital is a very noisy hematological cancer unit in a relatively new building of a large medical campus. Because of the requirements for dealing with immuno-suppressed patients, options for introducing sound absorbing materials are limited. In this article, a case study of noise control in a hospital, the sound environment in the unit before treatment is described, the chosen noise control approach of adding custom-made sound absorbing panels is presented, and the impact of the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…Preliminary research on the use of special sound-absorbing materials in ICU's confirms the positive impacts of this measure. 28,42 Another cost-effective alternative is the use of earplugs or earmuffs, which has also been subjected to research. 43,44 It should be noted that this measure only applies to hospital patients and not to hospital staff.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary research on the use of special sound-absorbing materials in ICU's confirms the positive impacts of this measure. 28,42 Another cost-effective alternative is the use of earplugs or earmuffs, which has also been subjected to research. 43,44 It should be noted that this measure only applies to hospital patients and not to hospital staff.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that installing sound-absorbing ceiling tiles and panels results in reduced noise levels and perceptions of noise leading to improved speech intelligibility and reduced perceived work pressure among staff (Blomkvist et al, 2005;MacLeod et al, 2007). Single-bed rooms are probably the single most-effective strategy for reducing noise in wards (Joseph and Ulrich, 2007).…”
Section: Recommendationsmentioning
confidence: 98%
“…Another effective strategy in controlling the levels of sound absorption is considered. In a study using fiberglass acoustic panels on the ceiling and walls of the oncology section 5 dB of ambient noise level was reduced (19,20).…”
Section: Discussionmentioning
confidence: 99%